KH. Muhammad Rosyad: Pendakwah Islam di Kecamatan Martapura Kota Kabupaten Banjar Tahun 1939-2000 - Perdana, Muhammad Putra Wahyu; Sriwati, Sriwati; Mansyur, Mansyur (Prabayaksa: Journal of History Education, 2021)
South Kalimantan is a province where the majority of the population holds strong Islamic teachings. This is evidenced by the large number of ulama who are scattered in almost all areas in South Kalimantan, therefore the Banjar community is known as a strong community holding the religion of Islam because of the existence of ulama who have influence and a large role in society. The research objective was to describe the biography of a ulama from Martapura named KH Muhammad Rosyad and to explain his role as a ulama in Martapura Subdistrict Kota Banjar Regency in 1939-2000. The research method used is the historical method. The steps taken in this research are heuristics or data collection through the interview method. The second stage is data criticism. The third stage is interpretation, and the last stage is historiography, namely writing the research results. The results showed that KH Muhammad Rosyad was born from the marriage of KH. Ahmad Zaini and Hj. Noorjanah on April 15, 1939, and died on Thursday, June 8, 2000 at the age of 63. The role of KH Muhammad Rosyad in preaching is that he opens a routine recitation every Wednesday night. He is also a lecturer at the Darussalam Martapura Islamic Boarding School, Datu Kalampayan Bangil and the College of Sharia Sciences. He is one of the scholars whose words and actions are in harmony in fostering the ummah, this is evidenced by him establishing a financial institution called BMT Al-Karomah Martapura Sharia Cooperative which still exists today with the aim of helping the economy of the people, especially the people of Martapura.